2013
DOI: 10.1007/s00701-013-1818-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of typical peripheral schwannomas: the risk of new postoperative deficits

Abstract: Although relatively infrequent, the potential for novel post-operative deficits after the surgical treatment of peripheral schwannomas does exist and should be included during pre-operative counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
43
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 23 publications
2
43
4
Order By: Relevance
“…Firstly, this location of schwannoma is extremely rare in clinical practice. In the upper limb, these tumours are most commonly located in the ulnar, median and radial nerves, being significantly rarer in the musculocutaneous and axillary nerves [1,3,5,6,18]. In our For this reason, dysfunction of the medial cutaneous nerve of the arm does not cause evident discomfort in patients, in contrast to impairment of function of other nerves [2,16,20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Firstly, this location of schwannoma is extremely rare in clinical practice. In the upper limb, these tumours are most commonly located in the ulnar, median and radial nerves, being significantly rarer in the musculocutaneous and axillary nerves [1,3,5,6,18]. In our For this reason, dysfunction of the medial cutaneous nerve of the arm does not cause evident discomfort in patients, in contrast to impairment of function of other nerves [2,16,20].…”
Section: Discussionmentioning
confidence: 99%
“…Levi et al observed new, postoperative neurological deficits in 41% of their patients who had previously been subjected to such procedures (biopsy or operation) at the surgical site [12]. It is also important to be aware that the results obtained after biopsy are not always identical to the results of histopathological examination of the surgically removed tumour [1,[17][18][19]. It has been suggested that biopsy is recommended in case of a suspected malignant lesion [3,14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…new neurological deficits could develop. 8) In the majority of cases, even when the tumor is carefully dissected from the involved nerve, incomplete nerve palsies sometimes occur. Levi et al 9) reported an 25.3% incidence of postoperative neurologic deficits in patients who had previously undergone schwannoma excision.…”
mentioning
confidence: 99%